Pengaruh Pengungkapan Media, Kinerja Lingkungan Dan Kepemilikan Asing Terhadap Pengungkapan Corporate Social Responsbility: - Bima Dwi Darma; Fefri Indra Arza; Halmawati Halmawati (Universitas Negeri Padang, 2019)
This study aims to see the effect of media exposure, environmental performance, and foreign ownership to corporate social responsibility disclosure. The population in this study are all mining companies listed on the Indonesia Stock Exchange (BEI) that is as many as 41 companies. The sample in this research use sampling technique purposive sampling counted 36 company. The analysis was done by using multiple regression model. The results of this study indicate that: (1) Media Exposure effect the disclosure of corporate social responsibility. (2) environmental peformance has no effect on corporate social responsibility disclosure. (3) foreign ownership has no effect on corporate social responsibility disclosure